Palmitoylation of gephyrin controls receptor clustering and plasticity of GABAergic synapses. - Borislav Dejanovic (Public Library of Science (PLoS), 2014)
Postsynaptic scaffolding proteins regulate coordinated neurotransmission by anchoring and clustering receptors and adhesion molecules. Gephyrin is the major instructive molecule at inhibitory synapses, where it clusters glycine as well as major subsets of GABA type A receptors (GABAARs). Here, we identified palmitoylation of gephyrin as an important mechanism of strengthening GABAergic synaptic transmission, which is regulated by GABAAR activity. We mapped palmitoylation to Cys212 and Cys284, which are critical for both association of gephyrin with the postsynaptic membrane and gephyrin clustering. We identified DHHC-12 as the principal palmitoyl acyltransferase that palmitoylates gephyrin. Furthermore, gephyrin pamitoylation potentiated GABAergic synaptic transmission, as evidenced by an increased amplitude of miniature inhibitory postsynaptic currents. Consistently, inhibiting gephyrin palmitoylation either pharmacologically or by expression of palmitoylation-deficient gephyrin reduced the gephyrin cluster size. In aggregate, our study reveals that palmitoylation of gephyrin by DHHC-12 contributes to dynamic and functional modulation of GABAergic synapses.